Characteristics, Risk Factors, and Outcomes of Extracorporeal Membrane Oxygenation Use in Pediatric Cardiac ICUs: A Report From the Pediatric Cardiac Critical Care Consortium Registry. Issue 6 (June 2018) - Brunetti, Marissa A.; Gaynor, J. William; Retzloff, Lauren B.; Lehrich, Jessica L.; Banerjee, Mousumi; Amula, Venugopal; Bailly, David; Klugman, Darren; Koch, Josh; Lasa, Javier; Pasquali, Sara K.; Gaies, Michael
Abstract : Objectives: Cardiopulmonary failure in children with cardiac disease differs from the general pediatric critical care population, yet the epidemiology of extracorporeal membrane oxygenation support in cardiac ICUs has not been described. We aimed to characterize extracorporeal membrane oxygenation utilization and outcomes across surgical and medical patients in pediatric cardiac ICUs. Design: Retrospective analysis of the Pediatric Cardiac Critical Care Consortium registry to describe extracorporeal membrane oxygenation frequency and outcomes. Within strata of medical and surgical hospitalizations, we identified risk factors associated with extracorporeal membrane oxygenation use through multivariate logistic regression. Setting: Tertiary-care children's hospitals. Patients: Neonates through adults with cardiac disease. Interventions: None. Measurements and Main Results: There were 14, 526 eligible hospitalizations from August 1, 2014, to June 30, 2016; 449 (3.1%) included at least one extracorporeal membrane oxygenation run. Extracorporeal membrane oxygenation was used in 329 surgical (3.5%) and 120 medical (2.4%) hospitalizations. Systemic circulatory failure and extracorporeal cardiopulmonary resuscitation were the most common extracorporeal membrane oxygenation indications. In the surgical group, risk factors associated with postoperative extracorporeal membrane oxygenation use included younger age, extracardiac anomalies, preoperative comorbidity, higher Society of Thoracic Surgeons-European Association for Cardiothoracic Surgery category, bypass time, postoperative mechanical ventilation, and arrhythmias (all p < 0.05). Bleeding requiring reoperation (25%) was the most common extracorporeal membrane oxygenation complication in the surgical group. In the medical group, risk factors associated with extracorporeal membrane oxygenation use included acute heart failure and higher Vasoactive Inotropic Score at cardiac ICU admission (both p < 0.0001). Stroke (15%) and renal failure (15%) were the most common extracorporeal membrane oxygenation complications in the medical group. Hospital mortality was 49% in the surgical group and 63% in the medical group; mortality rates for hospitalizations including extracorporeal cardiopulmonary resuscitation were 50% and 83%, respectively. Conclusions: This is the first multicenter study describing extracorporeal membrane oxygenation use and outcomes specific to the cardiac ICU and inclusive of surgical and medical cardiac disease. Mortality remains high, highlighting the importance of identifying levers to improve care. These data provide benchmarks for hospitals to assess their outcomes in extracorporeal membrane oxygenation patients and identify unique high-risk subgroups to target for quality initiatives. Abstract : Supplemental Digital Content is available in the text.